Just practice and the beginning social practitioner : a thesis presented in partial fulfilment of the requirements for the degree of Master of Social Work at Massey University, Albany, New Zealand - Gray, Mary Katharine (Massey University, 2004)
This qualitative study looks at how beginning social practitioners have taken up the idea of social justice as an abiding principle for their social practice. Social justice is an aspiration for practice in the fields of counselling, community work and social work. This study explores the understandings and expectations held about this in the social practice literature and looks at how this commitment is developed through the eyes of a group of beginning practitioners. Six new graduates from the UNITEC Institute of Technology Bachelor of Social Practice (hereafter BSP) programme were interviewed for this research. The meaning that social justice has for these participants is discussed in the context of literature about social justice as it relates to the social practices of community work, counselling and social work. A model of social justice in relation to change that I have developed provides a framework for these discussions. The part that participants' personal stories and the contribution of the UNITEC BSP programme to the development of their commitments to 'just practice' form the other major parts of this study. The literature on the teaching of social justice is explored and provides a context for a review of the curriculum and teaching on the BSP programme. How social justice features and is taught within the BSP programme is discussed in some detail. For all participants, the BSP programme provided significant learning about social justice. The salient feature that emerges from the study is the way in which the BSP teaching programme crystallises the meanings of social justice for all participants. It inspires participants to take on social justice as both a desirable and attainable goal for their practice. This study has identified the need for more extensive research on this topic, here and in other countries, and from the perspective of minority cultures. Ways to strengthen the BSP programme and other teaching programmes in their teaching of 'just practice' are recommended. The provision of 'hands on' learning opportunities are proposed, along with more integrated teaching approaches and ensuring that practitioners are equipped with strategies to sustain their 'just practice' are proposed. Questions are put to the wider social services community about their part in the practice of social justice.
Keywords: Social justice; Social service